Transcending Ethnic and Religious Barriers in Decision-Making: A Case of a Muslim Women Civil Organisation in Nigeria - Sarumi, Rofiah Ololade; Faluyi, Olumuyiwa Temitope; Okeke-Uzodike, Obianuju E. (Frontiers in Psychology, 2019)
Globally, women have more access to positions of authority and participate more in decision-making, regardless of context and rank, than a few years back. This is because of on-going global campaigns supported by various national and international laws and declarations. Increasingly, women have been exercising their rights and obligations to actively participate in politics and become visible in governance. Within Nigerian society, the efforts of women in governance, especially in the pre-colonial era, cannot be overlooked. Over the years, women in Nigeria have moved from the back seat to the roles of bread-winners, decision-makers and leaders of their immediate families. Irrespective of these progressive developments, women’s contributions to national development still have minor impact on decisions that affect society as a whole, due to the perceived marginalisation which still holds strong in most developing countries like Nigeria. Cultural and social norms, glass ceiling effects, and other exclusionary factors continue to dictate relegation of the presence and voice of women to a lower rank in public life. Against this background, this paper attempts to shed light on the role of civil organisations in enhancing women’s participation in politics and decision-making in governance issues in Nigeria. The paper examines strategies employed by civil organizations in ensuring women’s equal contribution to matters affecting them and society, and the challenges facing their active participation in this political era. Using documented researched materials, the findings of the study show that women’s intellectual, religious and political capabilities are vital components of every society.